Becoming connected learners through personalized learning. Issue 2 (15th March 2021) - Porath, Suzanne; Hagerman, Dana
Abstract: Drawing from different orientations, personalized, learner-centered environments and connected learning are two frameworks that work well together to renew classrooms and schools to focus on the needs and interests of the learner and make connections between experience, content standards, disciplines, and the community. This case study describes one American Midwestern middle school's implementation of a personalized, learner-centered approach in one of its five 8th grade houses (groups). A connected learning framework is applied to data from student, parent, and teacher focus groups to demonstrate how personalized learning environments can support the development of connected learners who are active participants in their own learning that is drawn from their own interests and extends beyond the classroom. We applied the connected learning framework to demonstrate how personalized learning environments can support the development of connected learners who are active participants in their own learning that is drawn from their own interests and extends beyond the classroom.